Suku Bajo dalam Dinamika Interaksi di Kecamatan Bangkurung (1999-2013) - Gobang; Tonny Iskandar Mondong; Moh. Imron Rosidi (Jurnal Pendidikan, Sejarah, dan Budaya, 2026)
This study examines the dynamics of social interaction among the Bajo people in Bangkurung Subdistrict, Banggai Laut Regency, during the period 1999–2013, with the aim of analyzing social, economic, and cultural changes in the context of the development of the archipelago. The study employs a social history methodology through the stages of heuristics, source criticism, interpretation, and historiography, utilizing primary sources such as historical interviews and village documents, as well as secondary sources including scholarly literature, archives, and statistical publications. The results indicate that the 1999–2013 period represented a significant phase of transformation for the Bajo community, marked by increased social interactions with non-Bajo communities through trade, social activities, education, and village governance. Economic changes were evident in the shift from a subsistence-based pattern to a semi-commercial one, driven by the adoption of fishing technologies and the diversification of livelihoods. This transformation did not erase the Bajo people’s maritime cultural identity but rather shaped new patterns of adaptation that blend traditional values with the demands of modernization. This study contributes to the field of social history of coastal communities by positioning the Bajo community as active agents in the process of change.